DESIGN AND IMPLEMENTATION OF A MICROCONTROLLER BASED DUAL AXIS SOLAR RADIATION TRACKER (Nigerian Journal of Technology, 2016)
In this paper, an efficient microcontroller-based dual axis solar radiation tracker which can be used to align a single photovoltaic (PV) module or an array of module with the sun is implemented. It employs a dual axis tracking system in its control circuitry as against the popularly employed programmable logic array.  Performance analysis of the dual axis solar tracker was conducted in a test bed in Department of Electrical and Electronics Engineering, Federal University of Petroleum Resources, Effurun, Nigeria and results showed that the power output of the photovoltaic (PV) system had 58.4 % improvement when compared with the traditional method of fixed solar panel. The dual axis system also has the benefit of reduction in the number of solar panels to be deployed because of the gains in power output and efficiency.  http://dx.doi.org/10.4314/njt.v35i3.17